PENGARUH VARIASI TEKANAN AIR TERHADAP PUTARAN TURBIN DAN DAYA OUTPUT YANG DIHASILKAN PROTOTYPE PLTMH MENGGUNAKAN TURBIN TURGO - I Made Suwartama Wijaya; I Wayan Arta Wijaya; I Gusti Ngurah Janardana (Jurnal SPEKTRUM, 2022)
Turgo turbine|is}one^type^of|impulse^turbine{that{is often used!in MHP (Microhydro Power Plant) which has a high head due to the sharp curvature of the blade. The case in turgo turbines is that{the|head!is?still)incorrect, because:this^type^of{turbine{uses*a!high(head-to<rotate^the^turbine runner. Based on what was{described, it!is^necessary!to”make|a prototype of PLTMH>using turgo turbines, in|”order{to(be)able:to”carry|out air pressure effect tests to obtain maximum output and efficiency in PLTMH using turgo turbines. The quantitative experimental method is carried out by calculating the primary data obtained. Prototype?testing|in]this{research used^various air!pressures, including 5 psi, 9 psi, 13 psi, 17 psi, 21 psi, and 25 psi. Based on the results of the study, increasing the*value*of^air^pressure given will cause MHP performance to continue to)increase.|The[maximum output!obtained!is?when^the!water^pressure^is the greatest which is 25 psi which|produces:a|turbine rotation of 838 rpm|before being|coupled with a DC generator and 672.6 rpm after being coupled with a generator, the rotation of the generator is 938.4 rpm, generator. voltage is 8.55 volts, and generator current is 1.044 Ampere, Generator Power 8.93 Watt, Torque 0.127 Nm with turbine efficiency 1.08%.